2017
DOI: 10.1111/mec.14138
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering conjugative plasmid permissiveness in wastewater microbiomes

Abstract: Wastewater treatment plants (WWTPs) are designed to robustly treat polluted water. They are characterized by ceaseless flows of organic, chemical and microbial matter, followed by treatment steps before environmental release. WWTPs are hotspots of horizontal gene transfer between bacteria via conjugative plasmids, leading to dissemination of potentially hazardous genetic material such as antimicrobial resistance genes (AMRGs). While current focus is on the threat of AMRGs spreading and their environmental main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 101 publications
(146 reference statements)
8
60
0
Order By: Relevance
“…Other dynamic OTUs from Gemmatimonas, Devosia, and Sphingomonas were enriched in response to B63 or P142, indicating that direct/indirect social interaction processes such as microbial facilitation may be involved in biocontrol. Sphingomonas is a strictly aerobic bacterium often characterized as an environmental oligotroph (Lauro et al, 2009;Jacquiod et al, 2017). Some Sphingomonas strains were shown to produce indole acetic acid (IAA), while others displayed phenazine degradation capabilities (Ma et al, 2012;Sukweenadhi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other dynamic OTUs from Gemmatimonas, Devosia, and Sphingomonas were enriched in response to B63 or P142, indicating that direct/indirect social interaction processes such as microbial facilitation may be involved in biocontrol. Sphingomonas is a strictly aerobic bacterium often characterized as an environmental oligotroph (Lauro et al, 2009;Jacquiod et al, 2017). Some Sphingomonas strains were shown to produce indole acetic acid (IAA), while others displayed phenazine degradation capabilities (Ma et al, 2012;Sukweenadhi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to tag-encoded 16S rRNA gene sequencing, the 24 samples of extracted DNA were subjected to an initial PCR amplification step using a set of primers, 341F and 806R ( Supplementary Table S1), which flank the approximately 460 bp variable V3-V4 region of the 16S rRNA gene of the target group Prokaryotes including domains of Bacteria and some Archaea. A second amplification step of the corresponding 16S rRNA gene region using the same primers with attachment of adaptors and barcode tags was done as previously described (Jacquiod et al, 2017). Purification and size selection (removal of products of less than 100 bp) of the approximately 620 bp PCR amplicon products was performed using Agencourt AMPure XP beads (Beckman Coulter, Brea, CA, United States) according to the manufacturer's instructions.…”
Section: Confirmation Of the In Planta Biological Control Of Ralstonimentioning
confidence: 99%
“…Moreover, Arcobacter has shown resistance to several antibiotics [41] and it has been proposed to be involved in the exchange of resistance genes between gramnegative and gram-positive phyla [43]. Notwithstanding, reports in Peru on the pathogenicity of this genus are scarce, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These genera have often been reported as carriers of antibiotic resistance plasmids in either environmental or clinical settings, such as plasmid mediated carbapenem- and colistin-resistance in Proteus and Providencia isolates. Recent studies have demonstrated the high potential of Aeromonas in carrying multidrug-resistance plasmids [4446], and in transferring plasmids in various environmental communities [2325]. Given the ubiquitous presence of Aeromonas in aquatic environments [47,48], Aeromonas might play a significant role in facilitating transfer and maintenance of plasmid-mediated ARGs in environmental communities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on community permissiveness (i.e., the ability to take up a plasmid from an exogenous donor strain) has revealed that IncP-1 plasmids can readily be transferred to diverse members of complex environmental communities [2325]. However, it is not clear to what extent the communities can maintain the plasmid and in which way the individual members can contribute to community-level plasmid persistence.…”
Section: Introductionmentioning
confidence: 99%